2004
DOI: 10.1238/physica.topical.107a00182
|View full text |Cite
|
Sign up to set email alerts
|

Sheared-Flow-Driven Electrostatic Waves in Laboratory and Space Plasmas

Abstract: Electrostatic turbulence covering a rest-frame frequency range from zerofrequency (D'Angelo and Kelvin-Helmholtz instabilities) to lower-hybrid frequency (Electron-Ion Hybrid instability) can be driven by shear in either the magnetic-field-aligned (parallel) or perpendicular velocity. Ion-acoustic, drift, and ion-cyclotron instabilities are significantly modified by velocity shear. Predictions from local and nonlocal models have been benchmarked by laboratory experiments and applied to interpretations of space… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 86 publications
0
13
0
Order By: Relevance
“…Interestingly, laboratory experiments demonstrated that ion temperature anisotropy can significantly increase the growth rate of shear-driven ion-acoustic (IA) waves (Koepke, 2004;Koepke et al, 2003). The increase in the growth rate with thermal anisotropy suggests that the plasma was unstable to smaller critical drifts.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, laboratory experiments demonstrated that ion temperature anisotropy can significantly increase the growth rate of shear-driven ion-acoustic (IA) waves (Koepke, 2004;Koepke et al, 2003). The increase in the growth rate with thermal anisotropy suggests that the plasma was unstable to smaller critical drifts.…”
Section: Introductionmentioning
confidence: 99%
“…Under that condition, we have jz e j ( 1, and the term De e (k, x), which determines the effect of electron Landau damping, may be neglected in Eq. (12). The negative term containing the ion diamagnetic drift velocity in Eq.…”
Section: Hydrodynamic Ionsmentioning
confidence: 99%
“…INTRODUCTION Shear in magnetic-field-aligned (i.e., parallel) plasma flow can be found in space, 1-3 fusion, 4-8 and laboratory [9][10][11][12][13][14][15][16] plasma. Ionospheric regions of inhomogeneous parallel plasma flow can map magnetically to magnetospheric regions of large-scale field-aligned currents, resulting in broadband electrostatic noise in the auroral zone of geospace.…”
mentioning
confidence: 99%
“…Sheared plasma flows parallel and perpendicular to the equilibrium magnetic field direction are ubiquitous in space and laboratory [1][2][3][4][5][6] and are considered to play an important role in the generation of plasma instabilities and turbulence. Long ago, 7 it was pointed out that the sheared plasma flow parallel to the external magnetic field can give rise to a purely growing electrostatic instability.…”
Section: Introductionmentioning
confidence: 99%